Trifluridine-tipiracil in previously treated patients with oestrogen receptor-positive, HER2-negative metastatic breast cancer (BOOG 2019-01 TIBET trial): a single-arm, multicentre, phase 2 trialResearch in context - Niels A.D. Guchelaar; Ron H.J. Mathijssen; Maaike de Boer; Marlies L. van Bekkum; Joan B. Heijns; Birgit E.P.J. Vriens; Mandy M. van Rosmalen; Lonneke W. Kessels; Lisanne Hamming; Karin J. Beelen; Peter Nieboer; Susan M. van den Berg; et al. (EClinicalMedicine)
Summary: Background: Effective later-line chemotherapy treatment options are scarce for patients with metastatic breast cancer (MBC). Trifluridine-tipiracil has shown survival benefit in heavily pre-treated patients with metastatic colorectal and in gastric cancer refractory to a fluoropyrimidine. This study aimed to investigate the efficacy of trifluridine-tipiracil in a Western population of previously treated patients with oestrogen receptor (ER+), HER2− MBC to facilitate further optimization of this treatment strategy. Methods: Adult patients at least 18 years old diagnosed with hormone receptor positive, HER2− receptor negative MBC with a performance status of 0 or 1 who have been treated with capecitabine in the metastatic setting and up to two other lines of chemotherapy, including a taxane, were enrolled in this single-arm, multicentre, phase 2 study in the Netherlands. The participants received trifluridine-tipiracil 35 mg/m2 orally twice a day on days 1–5 and days 8–12 during a 28-day cycle until disease progression, unacceptable toxicity, or withdrawal of consent. The primary endpoint was the disease control rate (DCR) at 8 weeks, defined as the percentage of patients that had stable disease, partial response or complete response according to RECIST 1.1, in all patients that received at least one dose of trifluridine-tipiracil and met the key eligibility criteria defined a priori. Secondary endpoints included progression-free survival (PFS), overall survival (OS), safety, and quality of life and were performed in all patients that received at least one dose of trifluridine-tipiracil. The primary endpoint was considered met, justifying further research of this treatment regimen, if the lower boundary of the 80% confidence interval (CI) exceeded 30%. The study was registered within ClinicalTrials.gov (NCT04489173) and is closed for inclusion. Findings: Fifty female patients were enrolled from September 2020 to July 2023, with a median of 3 (IQR, 2–3) previous endocrine therapy lines and 2 (IQR, 2–3) chemotherapy lines for MBC. The DCR rate at 8 weeks was 64.0% (n = 32, 95% CI: 50.1–75.9%; 80% CI: 55.0–72.1%), thereby meeting the primary endpoint of this study. At data cutoff (January 8, 2024), the median follow-up time was 18.2 months (IQR, 13.1–25.1 months). The median PFS was 5.4 months (95% CI: 2.0–7.2 months) and the median OS 14.0 months (95% CI: 8.8–17.8 months). The safety profile of trifluridine-tipiracil aligned with expected toxicities and included leukopenia (n = 36, 69%), neutropenia (n = 43, 83%), and fatigue (n = 43, 83%). The most common grade 3–4 AEs were primarily haematological disorders and included neutropenia (n = 38, 73%), leukopenia (n = 15, 29%) and anaemia (n = 6, 12%). The most common SAEs (any grade) with a possible relationship with trifluridine-tipiracil included anaemia (n = 2) and vomiting (n = 2). No treatment-related deaths occurred. Quality of life scores remained stable throughout the treatment. Interpretation: Trifluridine-tipiracil demonstrated promising efficacy in heavily pre-treated patients with MBC, despite prior exposure to a fluoropyrimidine. Clinically, this suggests that trifluridine-tipiracil holds potential as a viable oral later-line treatment option with a manageable toxicity profile while maintaining quality of life. Preparations for a phase 3 trial are underway. Funding: Servier, France.